Comparison of extraction techniques on extraction of gallic acid from stem bark of Jatropha curcas - Amirah; Reddy Prasad, D. M.; Khan, Maksudur R. (Asian Network for Scientific Information, 2012)
In this study, effectiveness of three different commonly applied extraction techniques for the determination of gallic acid in the stem bark of Jatropha curcas has been compared. The three different techniques that were used are namely as Soxhlet extraction, Ultrasonic-Assisted Extraction (UAE) and Microwave-Assisted Extraction (MAE). Quantification of gallic acid in the extracts was done using HPLC. In general, all extraction techniques were capable of extracting gallic acid from the stem bark, but the recovery obtained using modern extraction techniques was higher than using conventional extraction techniques. In particular, MAE extracts presented a higher amount of gallic acid than Soxhlet and UAE extracts. Therefore, MAE was a simple and rapid technique that was useful for extraction of Jatropha curcas stem bark. In contrast, Soxhlet extraction only results in slightly ruptured cell pores, which could explain its low amount of gallic acid produced.